Characterization of V-type asteroids orbiting in the middle and outer main belt. Issue 2 (10th February 2021) - Migliorini, Alessandra; De Sanctis, M C; Michtchenko, T A; Lazzaro, D; Barbieri, M; Mesa, D; Lazzarin, M; La Forgia, F
ABSTRACT: We present new spectral observations using ground-based telescopes of 23 putative V-type asteroids, selected according to colour surveys in the visible from the Moving Objects Catalogue of the Sloan Digital Sky Survey and near-infrared from the Moving Objects VISTA catalogue. 10 asteroids are orbiting in the middle main belt, while five in the outer part of the main asteroid belt. For the observed asteroids, we assign a taxonomical classification and confirm the basaltic nature for 16 of them. The high-quality spectra in the UV range, obtained with the X-Shooter spectrograph at ESO, allowed the identification of the Fe 2+ forbidden transition of pyroxene for 10 asteroids. This band is centred at 506.5 nm, and it is diagnostic of the Ca-content in the pyroxene form. We determined a low Fe-content composition for asteroids (2452) Lyot, (5758) Brunini, (7675) Gorizia, (9197) Endo, (22308) 1990 UO4, (36118) 1999 RE135, (66905) 1999 VC160, and (189597) 2000 WG119, and a composition more rich in Fe for asteroids (75661) 2000 AB79 and (93620) 2000 UQ70. We also present a dynamical investigation of V-type asteroids in the middle and outer main belt. The principal finding of these simulations is that the middle and outer V-types are more likely to be associated with some families, which were considered as possibly originated from the break up of a partially or totally differentiated parent body by diverse studies. This reinforces the hypothesis that the identified V-type in the region were not originated from (4) Vesta and that the number of differentiated objects in the middle and outer main belt must have been much larger than previously assumed.